Men of honor - Tillman, George (Madrinan, Diliman Quezon City : Viva Video, 2000)
Carl Brahser played by Cuba Gooding, Jr., lets nothing stand in his way. The son of a Kentucky sharecropper, Carl leaves home for what he expects would be a better life. " Never quit... be the best," his father told him, and Carl takes those words to heart. He joins the newly integrated Navy and applies to become a navy diver in the elite division used for search and rescue. Carl's training officer, billy Sunday, played by Robert DeNiro, wants no part of Carl or his ambitions. He drives Carl beyond the level of normal endurance in an attempt to get him to falter and quit. Overtime, the two men establish a respect that will ultimately see them battling alongside each other as they must fight to protect their honor and their lives. Starring Academy Award winning actors, Cuba Gooding, Jr. and robert DeNiro, MEN OF HONOR is an inspirational story about human spirit and determination.